Anxiety and Depression Prevalence and Risk Factors Among Patients With Cardiovascular Diseases in Post-COVID-19 China - Wu, Minglan; Shen, Liying; Wang, Qiqi; Liu, Li; Lu, Sen; Jin, Jianmei; Dai, Zhen; Shu, Zheyue (Frontiers in Public Health, 2022)
Objective: Data are limited on the psychological disorders of patients with cardiovascular disease during the post-COVID-19 period, although mental health status is associated with morbidity and mortality. We aimed to investigate the prevalence of anxiety and depression and risk factors among patients with cardiovascular disease in the post-pandemic period. Method: A cross-sectional survey was conducted through opportunistic and snowball sampling in southeast China from 10 October to 24 November. Anxiety and depression were assessed on the hospital anxiety and depression scale (HADS). Results: A total of 435 patients with hypertension (48.05%), atrial fibrillation (17.24%), coronary artery disease (14.48%), heart failure (9.89%) and other heart diseases (10.34%) completed the survey. Interestingly, most patients reported monthly income comparable to (90.11%) or even greater than (8.51%) pre-pandemic income. The occurrence of anxiety and depression was 11.72% and 9.20%, respectively. Marital status and treatment interruption during the pandemic were independent risk factors for both anxiety and depression. Moreover, current monthly income and access to telemedicine during the pandemic were independent risk factors for anxiety. Conclusion: Patients with cardiovascular disease may experience anxiety and depression not only because of disease complications but also because of the effects of the pandemic. In facing the global challenge posed by the coronavirus, efforts should be made to improve patients’ psychological well-being in the management of populations with cardiovascular disease.